2012
DOI: 10.1038/srep00254
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine phosphoglycerol attachment to eEF1A is not essential for normal growth of Trypanosoma brucei

Abstract: Eukaryotic elongation factor 1A (eEF1A) is the only protein modified by ethanolamine phosphoglycerol (EPG). In mammals and plants, EPG is attached to conserved glutamate residues located in eEF1A domains II and III, whereas in the unicellular eukaryote, Trypanosoma brucei, a single EPG moiety is attached to domain III. A biosynthetic precursor of EPG and structural requirements for EPG attachment to T. brucei eEF1A have been reported, but the role of this unique protein modification in cellular growth and eEF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The results showed that neither HsEF1A nor ScEF1A were able to complement the growth defect of TbEF1A-depleted T. brucei , whereas TbEF1A fully restored growth ( Fig. 2A , see also [20] ). Complementation of TbEF1A was further studied by conditionally expressing eEF1A from L. major (LmEF1A) in the C5 cell line, which is highly homologous to TbEF1A, differing in only 25 amino acids ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The results showed that neither HsEF1A nor ScEF1A were able to complement the growth defect of TbEF1A-depleted T. brucei , whereas TbEF1A fully restored growth ( Fig. 2A , see also [20] ). Complementation of TbEF1A was further studied by conditionally expressing eEF1A from L. major (LmEF1A) in the C5 cell line, which is highly homologous to TbEF1A, differing in only 25 amino acids ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Based on the above mentioned observations, we decided to investigate if HsEF1A and ScEF1A are able to complement T. brucei eEF1A (TbEF1A) function. In a previous study, we generated a tetracycline-inducible T. brucei cell line (named C5) in which expression of TbEF1A was ablated using RNAi, resulting in growth arrest of the parasites [20] . In the same work, we showed that growth could be fully restored by expressing an inducible ectopic copy of TbEF1A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations